Kajian Farmasi Klinis Penggunaan Obat Batuk “X” Dengan Kandungan Bromheksin HCl Untuk Pengencer Dahak Pada Anak - Lisna Nur Imani; Keri Lestari; Wida Mulyaningsih (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Cough is a physiological reflex that occurs to protect the lungs from mechanical trauma or a natural defense process to maintain the respiratory tract by preventing the ingress of foreign bodies in the respiratory tract. Children are particularly susceptible to a wide variety of diseases such as acute respiratory infections. There are 3 types of cough medicines sold freely in Indonesia, namely for coughing up phlegm, dry cough and allergic cough, where the drug content in each type of cough medicine is different. Cough medicine X is a sputum-thinning cough medicine containing bromhexine HCl that works to dilute sputum in the respiratory tract. This article contains clinical pharmaceutical studies related to cough medicine X with the active substance bromhexine HCl. Based on the results of clinical pharmaceutical studies, cough x medicine can be used as a treatment for cough phlegm in children.